Physico-chemical characterization of water-soluble pectic extracts from Rosa damascena, Calendula officinalis and Matricaria chamomilla wastes. (December 2016) - Slavov, Anton; Panchev, Ivan; Kovacheva, Daniela; Vasileva, Ivelina
Abstract: Water soluble pectic extracts were obtained from industrial wastes of three essential oil plants– Rosa damascena (rose), Calendula officinalis (marigold) and Matricaria chamomilla (camomile) as novel approach for valorization of these residues. The higher yield was observed for pectic extract isolated from waste rose petals–11%. Their chemical composition was investigated and was found that rose and marigold polysaccharides were medium methoxylated (DM around 50%) and camomile was low-methoxyl pectic extracts. The three pectic extracts had galacturonic acid content more than 50%. The lowest surface tension value showed pectic extract isolated from camomile wastes and it was comparable with beet and butternut pectins, guar and locust bean gums. The emulsifying properties (50% oil in water emulsions) of the isolated extracts were investigated. It was found that camomile pectic extract emulsions had the highest mechanical stability and marigold pectic extract derived emulsions were the least influenced by the storage temperatures. The data from differential thermal analysis (DTA) showed that the polysaccharide extracts were thermally stable until 220 °C. To our knowledge this is the first attempt for utilization of camomile and marigold wastes as source of pectic extracts and characterization of physico-chemical properties of water-soluble pectic extracts obtained from Rosa damascena, Calendula officinalis and Matricaria chamomilla residues. Graphical abstract: Highlights: Pectic extracts from rose, camomile and marigold wastes were obtained with yields 8–11%. The lowest surface tension–52.50 mN/m, showed pectic extract from waste of camomile. The three pectic extracts were thermally stable until 220 °C.